2011
DOI: 10.1093/epirev/mxr018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Race/Ethnicity in Alcohol-attributable Injury in the United States

Abstract: A substantial proportion of injuries worldwide are attributable to alcohol consumption, and US estimates indicate that the drinking patterns of racial/ethnic groups vary considerably. The authors reviewed evidence from 19 publications regarding racial/ethnic differences in overall alcohol-attributable injury as well as percent blood alcohol content positivity for injury deaths in the United States. They found that Native Americans evidence higher rates of alcohol-attributable motor vehicle crash fatality, suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 71 publications
5
65
0
2
Order By: Relevance
“…As expected (Bureau of Labor Statistics, 2014; Keyes et al, 2012), areas with greater population density, higher income, and more White residents had greater market potential for alcohol. The underlying theory therefore predicts that these areas will also have greater densities of alcohol outlets, except that outlets will be excluded from higher income areas, appearing in lower income areas near higher income areas.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As expected (Bureau of Labor Statistics, 2014; Keyes et al, 2012), areas with greater population density, higher income, and more White residents had greater market potential for alcohol. The underlying theory therefore predicts that these areas will also have greater densities of alcohol outlets, except that outlets will be excluded from higher income areas, appearing in lower income areas near higher income areas.…”
Section: Discussionsupporting
confidence: 72%
“…We have previously demonstrated that the geographic distribution of outlets is consistent with theory regarding these economic geographic processes in both urban and rural (Morrison, 2015) areas of Australia. Regarding racial and ethnic minority populations in the United States, it is clear that Black and Hispanic individuals are more likely to abstain from alcohol than White individuals and less likely to drink heavily (Keyes et al, 2012). They also spend a smaller proportion of their income on alcohol and spend less money overall on alcohol (Bureau of Labor Statistics, 2014).…”
Section: P Revious Studies Have Found That Areas In the Unitedmentioning
confidence: 99%
“…A review of the literature on the racial/ethnic disparity in rates of alcohol-attributable injury mortality suggests that although fatal consequences of excessive alcohol consumption are higher for Blacks and Hispanics compared with their White counterparts (Keyes et al, 2012), data for injury-specifi c fatalities have not been consistent. Risk of injury has been examined across all causes of injury, with alcohol having a greater association with some kinds of injuries compared with others Taylor et al, 2010), and may be a function of unmeasured individuallevel factors in additional to alcohol use, such as risk-taking disposition, occupational-related hazards, or exposure to environmental dangers, as noted above.…”
Section: Discussionmentioning
confidence: 99%
“…A review of racial/ethnic differences in injury mortality in the United States found that the rate of alcohol positivity and intoxication was disproportionately higher and alcoholattributable injury was overrepresented among Blacks and Hispanics compared with Whites (Keyes et al, 2012). This conclusion was based on the lower rates of alcohol use, binge drinking, and problem drinking found in epidemio-logic surveys of these two minority groups.…”
mentioning
confidence: 99%
“…The focus on NA young women is important because national behavioral, morbidity, and mortality statistics indicate that NA young women are a vulnerable group for alcohol-related consequences (Centers for Disease Control and Prevention, 2009;Chartier & Caetano, 2010;Eaton et al, 2010;Keyes et al, 2012;Russo et al, 2004;Wallace et al, 2003). Yet there is limited understanding of whether and how the etiology of alcohol use during adolescence may differ among NA compared with non-Native young women, which is needed to inform universal prevention efforts in multicultural communities.…”
Section: T His Study Provides New Information Tomentioning
confidence: 99%